Tradition is live and alive! The consumer experience in São João Festival in Campina Grande, Paraíba State - Cavalcanti, Rodrigo César Tavares; Lima, Mariana Patrícia de; Marques, Karina De Sousa; Nascimento, Joalline Carla Alves do; Oliveira, Adriana Maria de (Revista brasileira de marketing, 2025)
Objective: The aim of the current article is to describe the consumer experience at the traditional São João Festival, in Campina Grande, Paraíba State. Method: Interpretative Phenomenological Analysis was adopted as method, in association with theoretical elements available at the Consumer Experience literature. Results: Description highlighted four experiences as narratives comprising consumers’ reactions to the event: “Meeting an old friend again”, which is focused on affection to tradition; “Time to celebrate”, which is based on the existing bohemia;  “A northeastern feeling”, which is centered on local culture affirmation; and “It is no longer done like it was before…”, which expresses the critical tone facing traditions’ mutation. Contributions: The current study provides a sophisticated understanding about this experience, based on the Consumer Experience literature and on IPA application. Relevance: Innovative practical impact on both the involved public and private organizations. Socio-historical relevance as record of cultural manifestation featured by great popular engagement. Approach adopted to produce unique psychological descriptions about how people enjoy this festival. It was possible to understand nostalgic, pleasurable and identity-forming mechanisms shaping the experience with the event, among others. Social or managerial implications: Results make consumer experience innovation insights possible and are also a register of a high cultural-relevance event.